Computer simulation of transition modes in flow reactors considering the multistage and reactions non-perfectness - Kalbayeva, Aizhan Tazhikhanovna; Umarova, Zhanat Rysbayevna; Kurakbayeva, Sevara Dzhumagaliyevna; Musabekova, Leyla Mukhamedjanovna; Amandikov, Madamin A.; Arystanbayev, Kuttybek E. (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Due to the variety of reaction types and schemes in chemical-technological apparatuses, a general engineering methodology to assessing how the transient modes and reactions multi-stage act the kinetics in conditions of occurrence of moving reaction fronts in flow apparatuses has not yet been developed. The paper devotes to constructing the mathematical models for several important cases of the problem mentioned, namely: for theoretically study the kinetic dynamics of the conversion process in a three-stage chemical reaction with an autocatalytic first stage and the presence of a mass source of one of the components. An original mathematical model for describing the chemisorption dynamics at the initial stage of forming a moving reaction front in flow-through apparatuses has been developed. A special algorithm and numerical solution for the initial absorption period have been constructed, and appropriate computer simulation has been implemented. The significant influence of multistage on the formation and on stability types of stationary states has been established. Expressions to evaluate the characteristics of the emerging oscillatory modes have been obtained too. The results can be used to assess the influence of control parameters on the reaction front movement speed.